2013
DOI: 10.1007/s11064-013-1085-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Paraoxonase 2 (PON2) in Mouse Brain by the Polyphenol Quercetin: A Mechanism of Neuroprotection?

Abstract: Quercetin is a common flavonoid polyphenol which has been shown to exert neuroprotective actions in vitro and in vivo. Though quercetin has antioxidant properties, it has been suggested that neuroprotection may be ascribed to its ability of inducing the cell’s own defense mechanisms. The present study investigated whether quercetin could increase the levels of paraoxonase 2 (PON2), a mitochondrial enzyme expressed in brain cells, which has been shown to have potent antioxidant properties. PON2 protein, mRNA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 84 publications
2
46
0
Order By: Relevance
“…The hypothesis of sex differences was primarily based on recent findings in our laboratory on the differential expression of the enzyme paraoxonase 2 (PON2) between males and females (Giordano et al 2011; 2013; Costa et al 2014b). In brain and in other tissues, PON2 was shown to exert antioxidant and anti-inflammatory effects (Ng et al,, 2001; Horke et al, 2007; Giordano et al, 2011; Bourquard et al, 2011; Levy et al, 2007), and higher levels of PON2 are associated with decreased susceptibility to oxidative stress and neuroinflammation (Giordano et al 2013; Costa et al 2013). We found that females express higher levels of PON2 than males, possibly because this enzyme is modulated by estrogens (Giordano et al 2013; Costa et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of sex differences was primarily based on recent findings in our laboratory on the differential expression of the enzyme paraoxonase 2 (PON2) between males and females (Giordano et al 2011; 2013; Costa et al 2014b). In brain and in other tissues, PON2 was shown to exert antioxidant and anti-inflammatory effects (Ng et al,, 2001; Horke et al, 2007; Giordano et al, 2011; Bourquard et al, 2011; Levy et al, 2007), and higher levels of PON2 are associated with decreased susceptibility to oxidative stress and neuroinflammation (Giordano et al 2013; Costa et al 2013). We found that females express higher levels of PON2 than males, possibly because this enzyme is modulated by estrogens (Giordano et al 2013; Costa et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is a kind of flavonoid compound with biological activities. Abundant research in the past 10 years has confirmed the anti-tumor, anti-inflammatory, anti-platelet aggregation, anti-oxygen free radicals, and pro-vascular dilation properties of quercetin (Yao et al, 2011;Costa et al, 2013). In this study, the effects of quercetin on inflammatory factors, cell apoptosis, and oxygen free radicals in the myocardial tissue of AMI rats were investigated.…”
Section: Introductionmentioning
confidence: 81%
“…Because of the role of PON2 as a potent intracellular antioxidant and anti-inflammatory factor, strategies attempting to modulate its level of expression [20] should also consider sex and age as additional variables.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice have consistently higher levels of PON2 than male mice, most likely owing to the differences in estradiol between sexes, as PON2 expression appears to be modulated by estrogens [11]. The polyphenolic compound quercetin, a phytoestrogen, also modulates PON2 expression and may utilize similar signaling pathways as estrogen to influence PON2 transcription [20]. Also of relevance is that, in addition to differential susceptibility to oxidative stress between wild-type and PON2-null mice [10], significant differences in oxidant susceptibility have been associated with different levels of PON2 expression, exemplified by male and female differences in PON2 levels [11], or after positive modulation of PON2 by estradiol [11] or quercetin [20].…”
Section: Introductionmentioning
confidence: 99%